1992
DOI: 10.1007/bf00918977
|View full text |Cite
|
Sign up to set email alerts
|

Synergism among oxidants, proteinases, phospholipases, microbial hemolysins, cationic proteins, and cytokines

Abstract: A striking similarity exists between the pathogenetic properties of group A streptococci and those of activated mammalian professional phagocytes (neutrophils, macrophages). Both types of cells are endowed by the ability to adhere to target cells; to elaborate oxidants, hydrolases, and membrane-active agents (hemolysins, phospholipases); and to freely invade tissues and destroy cells. From the evolutionary point of view, streptococci might justifiably be considered the forefathers of "modern" leukocytes. Our e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 78 publications
(93 reference statements)
5
44
0
Order By: Relevance
“…Recent studies from our laboratories , Ginsburg and Misgav, 1992, Ginsburg and Mitra, 1993, Ginsburg, Kohen and Ligumsky, 1994, Ginsburg and Kohen, 1995a, have suggested that the killing of mammalian cells in infectious and in inflammatory sites might involve a well-orchestrated, synergistic 'cross-talk' among leukocyte-and microbial-derived oxidants, membrane-damaging agents and proteinases. While effective cell killing can be mediated by mixtures of oxidants and membrane-damaging agents, the release of significant amounts of membraneassociated lipids necessitates the additional presence of proteinases (Ginsburg and Mitra, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies from our laboratories , Ginsburg and Misgav, 1992, Ginsburg and Mitra, 1993, Ginsburg, Kohen and Ligumsky, 1994, Ginsburg and Kohen, 1995a, have suggested that the killing of mammalian cells in infectious and in inflammatory sites might involve a well-orchestrated, synergistic 'cross-talk' among leukocyte-and microbial-derived oxidants, membrane-damaging agents and proteinases. While effective cell killing can be mediated by mixtures of oxidants and membrane-damaging agents, the release of significant amounts of membraneassociated lipids necessitates the additional presence of proteinases (Ginsburg and Mitra, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…This raises serious questions whether histones are agents with a special role in pathogenicity; perhaps they are "regular" damage associated molecular pattern (DAMP) mediators, or perhaps just markers of tissue damage [2]. Of note, a synergistic toxicity to human umbilical cord endothelial cells in culture by histones combined with several pro-inflammatory agonists such as oxidants and proteinases has already been studied in detail many years ago by our group [11][12][13][14][15]. In fact, the proposition that the sepsis syndrome is derived from synergistic phenomena was already debated and presented in the year 2000 during a symposium at the Rockefeller Institute [22]; it is unclear to us why this proposition hasn't been studied more closely since.…”
Section: Synergistic Mechanisms Of Cell Damagementioning
confidence: 99%
“…This should be especially being the case if they were to be combined with cocktails of anti-inflammatory agents as suggested previously [11][12][13][14]. These may be anti-oxidants, proteinase, elastase and PLA2 inhibitors, and anticytokines and perhaps even IV-IgG.…”
Section: Journal Of Infectious Diseases and Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…This microorganism generates membrane-damaging toxins such as streptolysins O and S, intracellular hemolysin, proteinase and spreading enzymes such hyaluronidase, 4 RNAses, DNAse, super antigens, anti-phagocytic M-protein, cross reactive antigens and highly phlogistic peptidoglycan. It may therefore be argued, that synergism among a multiplicity of similar agents might also be the main cause of damage inflicted also in septic shock [25,26]. Several publications, which may have direct relevance to septic shock, were published along the years [27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: The Synergism Concept Of Cellular Injurymentioning
confidence: 99%